From the Editor - Judith A. Holton (Grounded Theory Review: An International Journal)
This issue of the Review explores several interesting perspectives on teaching and learning. First, we asked Dr. Glaser to revisit an address he gave a decade ago on the future of grounded theory. Just as a decade ago, he continues to suggest that the future of grounded theory rests with the novice grounded theorist attracted by the promise of finding out what’s really going on, of getting out into the field as soon as possible. As he points out, grounded theory often attracts a more mature individual; experienced practitioners pursuing a professional credentializing requirement as opposed to a purely scholastic pursuit. Many come from professional fields such as social work, nursing, medicine, allied health vocations, education, management and business. They’re practitioners seeking a better understanding of the social patterns that underpin the behaviours they encounter in their work – those high impact access and controllable variables (Glaser & Strauss, pp.245-249) that suggest better ways to mobilize often scarce resources to resolving issues or leveraging opportunities. There’s tremendous satisfaction in the emergence of such patterns in a research study. Perhaps somewhat intimidated by the standard academic prerequisites in qualitative research such as a declared philosophical stance, literature review and theoretical framework to guide the research, grounded theory’s straight forward, unencumbered and perhaps less pretentious and more intuitive approach provides a “sensitizing recognition” (Glaser, 1998, p.62) for the experienced practitioner. Easily overwhelmed by the social structural dictates of the academy, they understand and embrace a method that offers a ‘full package’ approach and promises an outcome with practical value.